Virtual Slant Explains Perceived Slant, Distortion, and Motion in Pictorial Scenes. (March 2013) - Erkelens, Casper J
Virtual slants of obliquely viewed figures consisting of skewed grids, computed as a function of depicted slant and slant of the physical surface, were compared with perceived slants in both monocular and binocular viewing conditions. Computations were based on an assumption of parallelism. Perceived slant was well-correlated with virtual slant, even though slants were generally underestimated. The qualitative relationship between virtual slants and physical surface slants was variable, and liable to produce different degrees and directions of apparent rotation as well as of apparent compensation, depending on the depicted slant of the stimulus. Contributions of screen-related cues were small and mainly limited to small slants. Remarkably, binocular disparity did not have any effect on perceived slant. The results imply that many past findings of both transformation and (apparent) compensation in pictorial viewing may in principle be straightforwardly explained as a function of the virtual stimulus.